PERSONAL HYGIENE PADA ANAK USIA SEKOLAH SUKU LAUT DUANO DI KECAMATAN KUNDUR KABUPATEN KARIMUN: Personal Hygiene for Suku Laut Duano Children in Kundur Sub-district - D Sitanggang, Hendra; Linnobi, Wardatunnajwa; Martias, Indra (Poltekes Kemenkes Tanjungpinang, 2021)
Personal hygiene for school-age children is a public health problem that still needs attention, including for the Suku Laut Duano children. The lack of implementation of personal hygiene in children can increase the risk of infection. The results showed that there was a relationship between personal hygiene and health problems. Therefore, it is necessary to know the application of personal hygiene in school-age children in the Suku Laut Duano. This study aimed to determine the description of personal hygiene based on skin hygiene, foot, hand, and nail hygiene, oral and dental hygiene, and hair hygiene. This research was a descriptive study using a cross-sectional design. Collecting data was carried out through interviews using a questionnaire. The population in this study were all school-age children, totaling 27 children. Data were analyzed by univariate. The results showed that the personal hygiene of the children was mostly in the poor category, both based on skin hygiene (66.7%), cleanliness of feet, hands, and nails (74%), oral hygiene, and teeth (66, 7%), and hair hygiene (70.4%). Poor personal hygiene can cause health problems in children. Therefore, the implementation of personal hygiene in children needs to be improved by involving parents and school.